Feeding ecology and sexual dimorphism in a speciose flower beetle clade (Hopliini: Scarabaeidae) - Colville, Jonathan F. (PeerJ, 2018)
The relationship between feeding ecology and sexual dimorphism is examined in a speciose South African monkey beetle clade. We test whether feeding and mating at a fixed site (embedding guild) is associated with greater levels of sexual dimorphism and possibly sexual selection than species using unpredictable feeding resources (non-embedding guild). Sexual dimorphism was measured using a point scoring system for hind leg and colour across the two feeding guilds for >50% of the regional fauna. Quantification of hind leg dimorphism using a scoring system and allometric scaling were used to identify traits subject to sexual selection. Feeding guild had a significant effect on hind leg dimorphism, with embedders having high and non-embedders low scores. The sessile and defendable distribution of females on stable platform flowers may favour contests and associated hind leg weaponry. In contrast, degree of colour dimorphism between the sexes was not associated with any particular feeding guild, and may serve to reduce male conflict and combat. Embedder males had high proportions (∼76%) of species with positive allometric slopes for almost all hind leg traits. For male non-embedders, only ∼37% of species showed positive scaling relationships. Phylogenetic data, in conjunction with behavioural data on the function of leg weaponry and visual signalling among males is needed to better understand the link between sexual dimorphism and sexual selection in the radiation of the monkey beetles.